Shortest path calculation using Dijkstra’s Algorithm. - Qing Zhu (349093) (2025)
The figure illustrates the shortest path from Node 0 to Node 9 in a road network modeled as a graph of charging stations. The optimal path, highlighted in red, minimizes travel time, passing through nodes 0 → 1 → 2 → 3 → 8 → 9 with a total travel time of 14 units. Edges represent roads between stations, and edge labels indicate travel time between nodes. Dijkstra’s algorithm efficiently computed the path, optimizing travel time for EV users.